Persepsi Preseptor Klinik Dan Komunitas Mengenai Peran Sebagai Pendidik Dalam Praktek Kerja Profesi Apoteker - Lingga, Herningtyas Nautika; Intannia, Difa; Khumaira Sari, Anna; Normaidah, Normaidah; Ikhwan Rizki, Muhammad (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
Preceptors are essential in guiding and being role models for students' knowledge, skills, and practices in implementing pharmacy internship program (PKPA) based on experiential learning. Guidance takes place in a clinical environment in a healthcare system that allows students to experience health services, interact with professional teams, and interact directly with the community. This study analyzes preceptors' perceptions regarding their role as educators in implementing PKPA. This study is a descriptive survey with a cross-sectional design using a questionnaire as an instrument. The study subjects were pharmacists who acted as preceptors in implementing PKPA with a purposive sampling technique. The data analysis used descriptive analysis. The results showed that of the 31 preceptors involved, the majority were female (74.19%), with an age range of 36-45 years (58.07%), and the place of practice was in a health center (58.07%). Preceptors' perceptions regarding the implementation of PKPA are generally positive. Aspects rated high with a score of more than 4 are the aspects of recognition/award, teamwork, communication, preparation, evaluation, appreciation, and the impact of student attendance. Meanwhile, the lowest ratings are in workload (3.75 ± 0.84) and facilities and infrastructure (3.86 ± 0.72). Preceptors provide positive perceptions about their role as educators in implementing the pharmacy internship program.